Broadband Hot‐Electron Collection for Solar Water Splitting with Plasmonic Titanium Nitride. Issue 15 (1st March 2017) - Naldoni, Alberto; Guler, Urcan; Wang, Zhuoxian; Marelli, Marcello; Malara, Francesco; Meng, Xiangeng; Besteiro, Lucas V.; Govorov, Alexander O.; Kildishev, Alexander V.; Boltasseva, Alexandra; Shalaev, Vladimir M.
Abstract : The use of hot electrons generated from the decay of surface plasmons is a novel concept that promises to increase the conversion yield in solar energy technologies. Titanium nitride (TiN) is an emerging plasmonic material that offers compatibility with complementary metal‐oxide‐semiconductor (CMOS) technology, corrosion resistance, as well as mechanical strength and durability, thus outperforming noble metals in terms of cost, mechanical, chemical, and thermal stability. Here, it is shown that plasmonic TiN can inject into TiO2 twice as many hot electrons as Au nanoparticles. TiO2 nanowires decorated with TiN nanoparticles show higher photocurrent enhancement than decorated with Au nanoparticles for photo‐electrochemical water splitting. Experimental and theoretical evidence highlight the superior performance of TiN in hot carrier collection due to several factors. First, TiN nanoparticles provide broadband absorption efficiency over the wavelength range 500–1200 nm combined with high field enhancement due to its natural cubic morphology. Second, TiN forms an Ohmic junction with TiO2, thus enabling efficient electron collection compared to Au nanoparticles. Since TiN nanoparticles have strong plasmon resonances in the red, the entire solar spectrum is covered when complemented with Au nanocrystals. These findings show that transition metal nitrides enable plasmonic devices with enhanced performance for solar energy conversion. Abstract : Plasmonic titanium nitride (TiN) provides two times larger generation of over‐barrier hot electrons than Au nanoparticles due to a broadband absorption and improved electrical compatibility at the TiN–TiO2 interface. TiN‐nanoparticle‐decorated TiO2 nanowires enhance the photo‐electrochemical water splitting activity compared to Au nanoparticles. This discovery enables the use of plasmonic nitrides in solar energy conversion.